2019
DOI: 10.1093/bmb/ldz023
|View full text |Cite
|
Sign up to set email alerts
|

Community-acquired acute bacterial meningitis in adults: a clinical update

Abstract: Background Acute bacterial meningitis (ABM) in adults is associated with a mortality that may exceed 30%. Immunization programs have reduced the global burden; in the UK, declining incidence but persistently high mortality and morbidity mean that clinicians must remain vigilant. Sources of data A systematic electronic literature search of PubMed was performed to identify all ABM literature published within the past 5 years. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…The clinical presentation of CABM varies and depends on the patient's age, coexisting conditions and comorbidities [15,[27][28][29][30][31]. Our study revealed the most common signs of CABMheadache, fever ≥38°C and nausea.…”
Section: Discussionmentioning
confidence: 63%
“…The clinical presentation of CABM varies and depends on the patient's age, coexisting conditions and comorbidities [15,[27][28][29][30][31]. Our study revealed the most common signs of CABMheadache, fever ≥38°C and nausea.…”
Section: Discussionmentioning
confidence: 63%
“…S. pneumoniae , an encapsulated, gram-positive bacterium, colonizes the nasopharynx. In rare circumstances, it accesses the bloodstream and may enter CSF [ 4 ]. Meningitis and bacteremia are forms of IPD, which is associated with an increased risk of permanent neurological sequelae and death [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Much rarer, intracranial extension causes otogenic intracranial sepsis and meningitis [ 8 ]. Bacterial meningitis, most often caused by S. pneumoniae , is associated with a 30% mortality rate in adults [ 4 ]. In one cohort study, S. pneumoniae caused 53.8% of 520 adult cases [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation